On the origin of the asymmetric dwarf galaxy distribution around andromeda. Issue 1 (12th December 2019) - Wan, Zhen; Oliver, William H; Lewis, Geraint F; Read, Justin I; Collins, Michelle L M
ABSTRACT: The dwarf galaxy distribution surrounding M31 is significantly anisotropic in nature. Of the 30 dwarf galaxies in this distribution, 15 form a disc-like structure and 23 are contained within the hemisphere facing the Milky Way. Using a realistic local potential, we analyse the conditions required to produce and maintain these asymmetries. We find that some dwarf galaxies are required to have highly eccentric orbits in order to preserve the presence of the hemispherical asymmetry with an appropriately large radial dispersion. Under the assumption that the dwarf galaxies originate from a single association or accretion event, we find that the initial size and specific energy of that association must both be relatively large in order to produce the observed hemispherical asymmetry. However if the association was large in physical size, the very high-energy required would enable several dwarf galaxies to escape from the M31 and be captured by the Milky Way. Furthermore, we find that associations that result in this structure have total specific energies concentrated around E = V_esc^2 - V_init^2 200^2 – 300^2 km^2 s^-2, implying that the initial velocity and initial position needed to produce the structure are strongly correlated. The overlap of initial conditions required to produce the radial dispersion, angular dispersion, and the planar structure is small and suggests that either they did not originate from a single accretion event, or that these asymmetric structures are short-lived.